Ovarian reserve analysis in subfertile women based on physical, ultrasound and hormonal parameters - Sudakshina Chakrabarti (Taylor & Francis Group, 2023)
Purpose: Despite the availability of several markers for the evaluation of ovarian reserve, the correlation between the markers has not been reported clearly in the existing studies. Therefore, this study investigated the level of subfertility by comparing the physical parameters such as age and BMI in the subfertile women. In addition, the study compared the ultrasound and hormonal parameters with the physical parameters in subfertile women.Methods: A total of 200 subfertile patients presented to outpatient department were considered in this study. The selected candidate was 29 to 39 years old and was investigated after two years of unprotected sexual intercourse. A consecutive enumerative sampling method has been employed for data collection. The collected data are processed to determine correlation and regression coefficients using Statistical Package for Social Sciences (SPSS) version 20.0.Results: The results revealed that follicle stimulating hormone (FSH) level and anti-Mullerian hormone (AMH) values varied among the above 30 age group of respondents with BMI values 25-30. There is no relationship between the respondents' right and left ovarian volume by comparing age within BMI.Conclusion: In conclusion, there is a strong relationship between the FSH level, AMH and physical parameters age and BMI. The reproductive age of women will be older than or younger than the actual age of the women. The reproductive age will be calculated with the ovarian volume, ovarian reserve, ovary size and time to menopause.